Description of Erythrocyte of Clarias gariepinus Infected by Aeromonas hydrophila and Treated with Bay Leaf Extract (Syzygium polyantha) - Cerlina, Maya; Riauwaty, Morina; Syawal, Henni (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Bay leaf (Syzygium polyantha) has antibacterial compounds like flavonoid, tannin, alkaloid, essential oil, vitamin C, and minerals. The purpose of this study was to obtain the best dose of bay leaf solution to cure catfish infected by Aeromonas hydrophila and seen from total erythrocytes, hemoglobin levels, hematocrit levels, and morphology of erythrocytes. The method used is an experimental method with a Completely Randomized Design (CRD), one factor with five treatments. The treatment applied is Kn (without immersed with bay leaf solution and not infected by A.hydrophila), Kp (without immersed with bay leaf solution and infected by A.hydrophila), P1 (100 ppm), P2 (1100 ppm), P3 (1200 ppm). The curing is done by immersed with bay leaf solution for 5 minutes, carried out three times with an interval of 24 hours. The results show that bay leaf solution able to cure catfish infected by A.hydrophila. The best dose is 1200 ppm with total erythrocytes was 244 x 106 cell/mm3, hemoglobin level was 11,67 g/dL, hematocrit level was 34,33% and the survival rate was 96,67%. Water quality during the study is temperature 27,3-28,0°C, pH 6,5-6,8, DO 3,4-4,2 mg/L and ammonia 0,016-0,019 mg/L.